INITIATIVES FOR IMPROVING THE PROVISION OF ASSISTANCE AT MEALTIMES FOR OLDER ADULTS ON HOSPITAL WARDS: A MIXED METHODS SYSTEMATIC REVIEW. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Edwards, Deborah; Hopkinson, Jane
Abstract : Background: In the UK, a third of older hospital patients are malnourished. Malnutrition is associated with staying in hospital longer, increased morbidity and mortality, especially for those with chronic conditions. Mealtime assistance may be important to improve nutritional intake, clinical outcomes and patient experience. Two previous quantitative systematic reviews have been undertaken. One explored the use of volunteers and the other feeding assistance in hospitals and care-homes. Aims: We are conducting the first mixed method systematic review about the provision of assistance at mealtimes for older adults on hospital wards to ▸ i) determine the effectiveness of interventions ▸ ii) explore the experiences of older adults and those involved with their care Methods: The design is informed by methods developed by the Evidence for Policy and Practice Information Centre. This 'mixed-methods' triangulation approach combines data from i) effectiveness studies, ii) studies which obtain the views of participants and iii) current guidelines and policy. We have conducted a search of electronic databases (CINAHL, MEDLINE, BNI, Cochrane Library, EMBASE, PsychINFO, Open-Grey). Limits were English language; 1996 to present; adults. Abstracts have been assessed against inclusion/exclusion criteria by two researchers to select full-text for quality assessment and data extraction. The key elements of best practice will be extracted from current guidelines and policy documents. This will be used to derive a framework to guide analysis and interpretation of the evidence. Results: The findings will be presented as a conceptual map of initiatives for improving the provision of assistance at mealtimes for older adults on hospital wards. We will also present propositions of what might be most effective in assisting oral mealtime nutritional intake and the implications. Conclusion: We are conducting a systematic evaluation of literature to provide recommendations for the supportive nutritional care of older malnourished chronically ill people in hospital.